2017
DOI: 10.18203/2394-6040.ijcmph20173332
|View full text |Cite
|
Sign up to set email alerts
|

Readiness for self-directed learning among undergraduate medical students of Andhra Medical College, Visakhapatnam

Abstract: Background: Self-directed learning (SDL) has been identified as an important skill for medical graduates. To meet the challenges in today's healthcare environment, self-directed learning is most essential. Readiness for SDL is the degree to which an individual possesses attitudes and abilities necessary for SDL. The present study was taken to assess the self-directed learning readiness (SDLR) among 4th semester medical students in a tertiary care teaching hospital. The objectives of the study were to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 7 publications
2
13
1
3
Order By: Relevance
“…[ 3 ] The readiness for SDL practices appeared to be low among medical students in India and the need to find ways to build SDL skills among them is of paramount importance. [ 21 22 23 ] Similarly, in our study, the adult learning principles (SDL and reflective learning) were not much appreciated by the students. Many felt that these principles were time-consuming and a few have also reported that these were not followed in their colleges.…”
Section: Discussionmentioning
confidence: 50%
“…[ 3 ] The readiness for SDL practices appeared to be low among medical students in India and the need to find ways to build SDL skills among them is of paramount importance. [ 21 22 23 ] Similarly, in our study, the adult learning principles (SDL and reflective learning) were not much appreciated by the students. Many felt that these principles were time-consuming and a few have also reported that these were not followed in their colleges.…”
Section: Discussionmentioning
confidence: 50%
“…In contrast, a study by Kar et al showed higher proportion of male students (60.9%). [6][7][8][9][10][11][12][13][14] With look to area of residence of the students, majority (68.0%) reside in urban locality in the current study. In the existing study, the mean SDLR score among study participants was 152.…”
Section: Resultsmentioning
confidence: 99%
“…Tại Ấn Độ, Madhavi et al, (2017) đánh giá mức độ sẵn sàng học tập tự định hướng của sinh viên y khoa trường đại học y Andhra, Visakhapatnam [33]. Nghiên cứu này giống như nghiên cứu của Alfaifi (2016) ở Arab Saudi, cũng tìm hiểu mối liên quan giữa sự sẵn sàng cho học tập tự định hướng và đặc điểm nhân khẩu học của sinh viên [32].…”
Section: Tổng Quan Nghiên Cứu Về đáNh Giá Mức độ Sẵn Sàng Học Tập Tự địNh Hướng Trên Thế Giớiunclassified
“…Các tác giả cho rằng điểm 'ham học hỏi' và 'tự chủ' cao hơn so với 'tự quản' thể hiện việc nhấn mạnh sự cần thiết người dạy cần phải tập trung vào kỹ năng này. Kết quả nghiên cứu cũng cho thấy "mặc dù một số sinh viên y khoa đã sẵn sàng cho việc học tập tự định hướng nhưng vẫn còn những sinh viên khác chưa sẵn sàng" [33]. Do đó, cần phải xem xét về các kỹ năng học tập tự định hướng của sinh viên và các biện pháp xây dựng và thúc đẩy các kỹ năng học tập tự định hướng ở sinh viên [33].…”
Section: Tổng Quan Nghiên Cứu Về đáNh Giá Mức độ Sẵn Sàng Học Tập Tự địNh Hướng Trên Thế Giớiunclassified
See 1 more Smart Citation